Characterizing Thermal Background Events for Athena X-IFU - Hull, S. V.; Adams, J. S.; Bandler, S. R.; Beaumont, S.; Chervenak, J. A.; Cumbee, R.; Finkbeiner, F. M.; Ha, J. Y.; Kelley, R. L.; Kilbourne, C. A.; Porter, F. S.; Sakai, K.; et al. (IEEE transactions on applied superconductivity, 2023)
The X-ray Integral Field Unit on Athena will be subject to a cosmic-ray induced thermal background on orbit, with energy depositions into the detector wafer leading to thermal bath fluctuations. Such fluctuations have the potential to degrade energy resolution performance of the transition-edge sensor based microcalorimeter. This problem was previously studied in simulations that modeled thermal bath fluctuations induced by cosmic-ray events and evaluated the resulting energy resolution degradation due to a simulated timeline of such events. Now taking an experimental approach, we present results using a collimated Am-241 alpha particle source to deposit a known energy to specific locations on the detector wafer. Thermal pulses induced by the alpha particle energy depositions are measured at various detector pixels for several different experimental configurations, including for energy deposited into the inter-pixel structure of the wafer, as well as the frame area outside the pixel array. Further, we also test both with and without a thick backside heatsinking metallization layer that is baselined for the instrument. In each case results are compared to expectations based on the thermal model developed for the previous study.